The Superhero in Post-9/11 Marvel Comics and Filipino Film - Javier, Carljoe (Silliman Journal, 2022)
This paper explores the use of the superhero as a symbol and how it comes to represent a culture’s morals. By focusing on the specific time period of post-9/11, it makes a comparative reading of the mainstream expression of superheroes in American and Philippine cultures, thereby building discourse on both the superhero as a symbol and its use in expressing each culture’s moral values.